PELESTARIAN HUTAN MANGROVE DI TELUK BENOA BALI: TINJAUAN DARI ASPEK EKONOMI LINGKUNGAN - I GUSTI BAGUS MADE WIRADHARMA; MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
Indonesia is known as the archipelago country, in which the islands are connectedby the sea. As the archipelago country Indonesia has a lot of good nature resources both inland including coastal area and in the sea, so that Indonesia is also known as maritimecountry. However, because the society does not have enough knowledge in managing themmany of the nature resources become damaged. This is also caused by the people in theirown activities for earning a living do not take care of the sustainability of the living andnon living resources and their ecosystem.The mountaineering area of Mangrove in Teluk Benoa Bali having the status as theforest preserve or protected forest named TAHURA Ngurah Rai, cannot avoid thepressures caused by the changes and the conversion. The mangrove forest tends to givebenefits for little society, but those societies actually decrease its support and its capacitysuch as; making fishpond, garbage disposal, housing, reclamation, fuel pipeline, etc. Thissituation, of course, decreases the better function and advantages of the mangrove forest inTeluk Benoa. It needs an analysis to determine the social benefits and economic value ofthe forest mangrove itself so that if it is conserved with the conservation scenario, which isin the future can be used by the policy maker for determining the management option, itwill be known if the land conversion of the mangrove can be done or allowed to happencontinuously?Then through the analysis of economic for environment by using investment, that isNet Present Value/NPV, B-C Ratio (also by considering the changes of condition ofsensitivity analysis) and total economic value especially for the purpose of preservationwith the conservation scenario it is concluded that the preservation of the mangrove forestgive social benefit of Rp. 94.288.557,59 per hectare a year and the increase investmentcost and routine is 10% and the decrease of the price is 5% giving social benefit of Rp.93.003.794,32 and Rp. 88.931.748,08. In normal condition the increase investment costand routine is 10% and the decrease of the price is 5% giving NPV in a row; Rp.831.903.896, 27; Rp. 818.526.222, 18 and Rp. 783.619.864,41 per hectare per year. Thesame condition like above gives B-C Ratio in a row; 7,22; 6,56 and 6,86. This shows thatin any kind of condition the preservation of the mangrove forest in Teluk Benoa Bali issuitable to do. The total value of the economic also shows the yearly asset value of thesociety in the form of nature resources/ mangrove forest of this area (1,373,5 hectare) is inthe three conditions; Rp.129.505.333.853,32; Rp.127.740.711.499,67 andRp..147.755.983,83 a year.According to those conclusion it can suggested that the function of mangrove forestin Teluk Benoa Bali can be managed accordingly so that the environmental function canrun well. Besides, economic value can be used as the reference for coastal management tosustainability.